April 2009 “Tri-elections” in Malaysia: maintaining the status quo - Mokhtar, Tunku Mohar (IIUM Press, 2009)
By-elections held after the 12th general elections held on March 8, 2008 are of special significance as they indicate the level of support gained by the opposition as well as the receding popularity of the ruling coalition. The three by-elections (hence called tri-elections), one parliamentary and two state assemblies, held in April 2009 show that the composition of the federal parliament and the state assembly of Kedah and Sarawak remained the same. The PR garnered multiethnic support in the peninsula while BN remains strong in Sarawak.